Proteolysis in Reproduction: Lessons From Gene-Modified Organism Studies - Kiyozumi, Daiji; Ikawa, Masahito (Frontiers in Endocrinology, 2022)
The physiological roles of proteolysis are not limited to degrading unnecessary proteins. Proteolysis plays pivotal roles in various biological processes through cleaving peptide bonds to activate and inactivate proteins including enzymes, transcription factors, and receptors. As a wide range of cellular processes is regulated by proteolysis, abnormalities or dysregulation of such proteolytic processes therefore often cause diseases. Recent genetic studies have clarified the inclusion of proteases and protease inhibitors in various reproductive processes such as development of gonads, generation and activation of gametes, and physical interaction between gametes in various species including yeast, animals, and plants. Such studies not only clarify proteolysis-related factors but the biological processes regulated by proteolysis for successful reproduction. Here the physiological roles of proteases and proteolysis in reproduction will be reviewed based on findings using gene-modified organisms.